The Analysis of Payment Compliance in Independent Participants of the National Health Insurance in Regional Hospital of Haji Makassar - Anggraeni, Faradiba; Indar; Syafar, Muhammad (International Journal of Psychosocial Rehabilitation, 2020)
The increasing participation in the National Health Insurance (JKN) program is out balanced with compliance of independent participants in paying the insurance premium. The objective of the study was to explore factors influencing compliance of independent participants of JKN in paying the insurance premium at Haji Hospital, Makassar. This study was a quantitative study with a descriptive survey approach. The population of the study was all independent participants of JKN at the outpatient installation of Haji Hospital, Makassar. The sampling technique used purposive sampling with a sample size of 97 people. The data was collected through interviews and analyzed using chi-square and logistic regression tests. The results of the study showed factors influencing compliance of JKN independent participants in paying insurance premium were income level, the human resources of BPJS Kesehatan (premium collector), and perception on health services (p<0.05). the human resources of BPJS Kesehatan who had collected the insurance premium was the most significant factor affecting compliance of premium payment. Independent participants of JKN are recommended to spend some of their income to pay the insurance premium and to the health service provider to enhance the quality of services, and BPJS Kesehatan should increase the socialization regarding alternative payment methods as well as improving media reminder of premium payment to JKN participants.